ผลของการฝึกโคคอนแทคชั่นแบบขาเดี่ยวที่มีต่อการทรงตัวของนักกีฬาแบดมินตันชาย - ศรัณย์ สุรวิริยาการ (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
Purpose: This experimental study aimed to study the effects of additional co-contraction training during standing on one leg, applied from star excursion pattern, in male Badminton players aged between 18-25 years. Twenty-four subjects were divided into two groups, control and experimental group. Static Balance test by The Overall Stability Index (OSI), Anterior/Posterior Index (API) and Medial/Lateral Index (MLI) were measured by using Biodex Balance System (Bio Sway) and Dynamic Balance test by Distance and Displacement. Pre and post training three times a week for 6 weeks were measured all parameters. Compared mean and standard deviation between pre and post training with Dependent t-test (repeated measure), and between groups with Independent t-test. The statistical significant was set at p<0.05. Results: The experimental group showed significantly decrease of stability index, additionally, decreased significantly more than in control group in all of stability index. Conclusion: The Additional co-contraction training, applied from Star excursion pattern, in male Badminton players three times a week for 6 weeks could enhance balance performance at all directions.